2020
DOI: 10.1186/s12917-020-02690-z
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of extensive hemilaminectomy with durotomy on dogs with presumptive progressive myelomalacia: a retrospective study on 34 cases

Abstract: Background Progressive myelomalacia (PMM) is a fatal complication of progressive ascending and descending necrosis of the spinal cord after acute spinal cord injury. A recent study suggested that extensive hemilaminectomy with durotomy (EHLD) at the intramedullary T2-hyperintense region which performed immediately after magnetic resonance imaging (MRI) improved the survival rate in dogs with presumptive PMM. The objective of this retrospective study was to evaluate the effects of EHLD on halting the progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
(66 reference statements)
2
10
0
Order By: Relevance
“…Postoperative survival rate was 61% for 18 dogs with focal hemilaminectomy alone, and EHLD was identified as the independent variable associated with increased survival using multivariate analysis. In a retrospectively reported case series of 34 dogs with presumed PMM and treated with EHLD of variable length, postoperative survival rate was 91% with a median follow‐up of 82.5 weeks 234 . No dogs in this series regained ambulation, but the authors attributed the high rate of postoperative survival to EHLD and attenuated PMM progression.…”
Section: Progressive Myelomalaciamentioning
confidence: 84%
See 2 more Smart Citations
“…Postoperative survival rate was 61% for 18 dogs with focal hemilaminectomy alone, and EHLD was identified as the independent variable associated with increased survival using multivariate analysis. In a retrospectively reported case series of 34 dogs with presumed PMM and treated with EHLD of variable length, postoperative survival rate was 91% with a median follow‐up of 82.5 weeks 234 . No dogs in this series regained ambulation, but the authors attributed the high rate of postoperative survival to EHLD and attenuated PMM progression.…”
Section: Progressive Myelomalaciamentioning
confidence: 84%
“…Conventional wisdom suggests that removal of numerous consecutive articular processes and their soft tissue attachments can result in decreased vertebral column stability, and, a recent retrospective study identified a negative association between prolonged anesthetic time and neurologic outcome in paraplegic DPN dogs 235 . However, a study describing very extensive laminectomy and durotomy for some animals (often >10 vertebral segments) reported that no dogs required spinal stabilization or developed serious complications or radiographic signs of instability 234 . One study did report a single case with short‐term severe allodynia that resolved within 10 days after treatment with PO gabapentin 99 …”
Section: Progressive Myelomalaciamentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical confirmation of myelomalacia by visual inspection of the spinal cord after durotomy and palpation with a probe may be considered sufficient to definitively diagnose myelomalacia. 34,35 Although irreversible, myelomalacia may remain focal from the start or halt after initial ascending/descending progression for largely unknown reasons, though measures to lower intraspinal pressure seem promising.…”
Section: Discussionmentioning
confidence: 99%
“…• The effect of extensive decompressive surgery and durotomy in dogs with severe SCI or myelomalacia is a subject of interest in recent literature. [34][35][36][37] • Dural surgery as a measure to lower intrathecal pressure and monitoring thereof are two of the key points of…”
Section: Discussionmentioning
confidence: 99%